A better assessment of personality in language-learning situations. (5th July 2017) - Karlin, Omar; Karlin, Sayaka
Abstract : Two hundred and sixty-two items, using a five-point Likert scale, were created and administered to 287 Japanese university students to measure five personality factors based on the extraversion, emotional stability, openness, agreeableness, and conscientiousness factors of the Big Five model of personality (McCrae and Costa, 1987). These items were then culled to 50 items by examining their suitability through factor analysis and Rasch analysis, resulting in two 50-item versions of the Questionnaire of English Environment Personality (QuEEP). Both versions of the QuEEP included 10 items for each of the five personality factors in the Big Five. Both versions of the QuEEP outperformed an established personality instrument not specifically intended for language-learning situations, the International Personality Item Pool Big Five Factor Markers test (IPIP BFFM), on five measures of validity, including content validity, the substantive aspect of construct validity, structural validity, external validity, and generalizability. As a result, it was concluded that the QuEEP, specifically the version derived from the Rasch analysis, was more effective than the IPIP BFFM at capturing personality situated in language-learning situations.